Sosialisasi Produk Bank Syariah Dalam Upaya Meningkatkan Literasi Masyarakat Akan Lembaga Keuangan Syariah di CFD Jalan Dhoho Kota Kediri - Caspirosi, Loris Caspirosi; Efendi, Rofik; Khasan, Nur; Anwar, Ahmad Saiful (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The Dhoho Car-Free Day event is a gathering place for people in the city of Kediri. This opportunity is used by Bank Jatim Syariah Kediri Branch in providing knowledge to the general public. With people who understand more about Islamic banks, the potential for Bank Jatim Syariah in developing and advancing the people's economy will also be great. The purpose of this socialization is to increase public knowledge, especially among Dhoho CFD visitors, regarding Islamic banks. Using socialization methods by holding exhibition stands and games The result of this socialization is that visitors who take part in it understand the outline and mechanisms of Islamic banking.